An Estimate of the Influence of the Compressor Stability Margin on the Pick-Up Time of a Turbojet Engine - M. Orkisz (Engineering Transactions, 1991)
The relations are derived enabling to estimate the acceleration time of the turbojet engine rotor set. The terms are established allowing for the determination of the effect of individual operational and structural engine parameters upon the time needed for acceleration of the rotor system. Influence of the economic and optimum ranges of operation upon that time is also analyzed.